2012
DOI: 10.1080/17470218.2012.658822
|View full text |Cite
|
Sign up to set email alerts
|

Predicting foreign-accent adaptation in older adults

Abstract: We investigated comprehension of and adaptation to speech in an unfamiliar accent in older adults. Participants performed a speeded sentence verification task for accented sentences: one group upon auditory-only presentation, and the other group upon audiovisual presentation. Our questions were whether audiovisual presentation would facilitate adaptation to the novel accent, and which cognitive and linguistic measures would predict adaptation. Participants were therefore tested on a range of background tests: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
93
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 94 publications
15
93
2
Order By: Relevance
“…Both for rule-based learning of novel categories (Nosofsky, 1986;Nosofsky, Gluck, Palmeri, McKinly, & Glauthier, 1994) and for learning of an artificial Dutch accent (Janse & Adank, 2012), better selective attention abilities were suggested to lead to better learning. In the context of lexically guided perceptual learning, we suggested that listeners with better selective attention may be drawn to the ambiguity of the target word's final sound, which would reduce the listener's susceptibility to lexically guided perceptual learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both for rule-based learning of novel categories (Nosofsky, 1986;Nosofsky, Gluck, Palmeri, McKinly, & Glauthier, 1994) and for learning of an artificial Dutch accent (Janse & Adank, 2012), better selective attention abilities were suggested to lead to better learning. In the context of lexically guided perceptual learning, we suggested that listeners with better selective attention may be drawn to the ambiguity of the target word's final sound, which would reduce the listener's susceptibility to lexically guided perceptual learning.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to have an impact on the recognition of accented speech (Adank & Janse, 2010;Gordon-Salant, YeniKomshian, & Fitzgibbons, 2010a, b;Janse & Adank, 2012). The particular effect of high-frequency hearing loss on lexically guided perceptual learning is however unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that have been suggested to account for this individual variation include differences in peripheral hearing thresholds (Humes, 2013), differences in receptive vocabulary (Janse and Adank, 2012;McAuliffe et al, 2013), and differences in working memory capacity (Gordon-Salant and Cole, 2016;R€ onnberg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of work has focused on the individual differences in the perception of the acoustic cues that define sound contrasts, and shown that this relation may vary as a function of factors such as language background (Escudero & Boersma, 2004;Schertz, Cho, Lotto, & Warner, 2015), cue weighting strategy (Beddor, McGowan, Boland, Coetzee, & Brasher, 2013;Kong & Edwards, 2011), as well as cognitive abilities (e.g. attention: Janse & Adank, 2012; working memory: Francis & Nusbaum, 2009; cognitive processing style: Stewart & Ota, 2008;Yu, 2010). Focusing on native sound contrasts, the purpose of the present investigation was to examine the cognitive factors that give rise to individual differences in perception and production of speech sounds.…”
Section: Introductionmentioning
confidence: 99%